Early intervention care programme for parents of neonates - W Lubbe (AOSIS, 2005)
Parents with neonates in the neonatal intensive care unit (NICU) experience different needs at different stages of their neonates' stay in the NICU. The needs of parents with neonates in NICU's play an important role in aspects such as the ability to cope with changing parental roles and emotions, the relationship between parent and infant and the managing of the parents' own needs. The aim of this study was to develop an intervention care programme for parents with neonates in the NICU. This intervention care programme will empower parents to manage their own needs and the needs of their neonates while the neonate is admitted to the NICU and after discharge from the NICU / hospital. Literature is available on care programmes for neonates, but not on programmes for the parents of neonates in NICU. The study was a multi-phased study, using qualitative methodologies to determine the needs of South African parents with neonates in level III NICU's. In phase I, the needs of parents with neonates in NICU were elicited qualitatively. The needs were identified from the data and the results led to the implementation of phase II. In phase II the question was adjusted and new data was collected. Phase III was implemented to validate the data derived from phases I and II. The data was categorised in different need categories and these categories were used to plan an intervention care programme for parents with neonates in NICU's. The programme provides information to address needs as identified by parents in the research study and as derived from the literature. Need categories identified from the study and literature were as follows: information, communication, emotional, learning, discharge and individual needs. This programme is available in electronic format to enable parents to obtain information according to their changing needs and to provide unlimited access to updated information. The "Early intervention care programme for parents of neonates" will empower parents to manage their own needs and the needs of their neonates while the neonate is admitted to the NICU and'after discharge from the NICU / hospital.